Key Role of Binders to Anchor Nanoparticle-Based Supraparticles on Spherical Substrates with Preserved Functionality - Zimmermann, Thomas; Fischer, Christopher; Oppmann, Maximilian; Wenderoth, Sarah; Winzer, Bettina; Somorowsky, Ferdinand; Vogel, Nicolas; Mandel, Karl; Wintzheimer, Susanne (ACS Applied Nano Materials, 2025)
Supraparticles, particles composed of individual nanoparticles, have attractive properties, but their applicability in real-world applications is often restricted by their comparably small dimensions. Suprabeads, in which individual supraparticles are fixed to a larger support bead with the help of a binder, have been proposed to address this challenge. These suprabeads retain the the unique functionalities of both the nanoparticles and supraparticles while offering millimeter-sized dimensions for facilitated handling. Here, we investigate the role of the binder in the formation and functionalization of suprabeads. First, we focus on the thermal, mechanical, and chemical stabilities of suprabeads as a function of their binder composition. Our results show that binders containing organic groups offer room-temperature curability, while the chemical and thermal stability of the resulting suprabeads is limited and their mechanical stability depends on the flexibility of the binder. Inorganic binders drastically increase the temperature stability but are inherently more brittle. Second, we demonstrate that wetting the supraparticle with the binder layer enables us to tailor the resultant suprabead functionality. While a low degree of embedding provides accessible supraparticles, a larger degree of embedding induces tunable protection of the supraparticles from the environment. To highlight the versatility of the suprabead concept, we demonstrate that the ideal binder material can be identified for a specific application, such as ammonia indication or propane dehydrogenation.
CRIS-Team Scopus Importer:2025-02-28
Keywords: binder; gas detection; mechanical stability; suprabeads; supraparticles